2017
DOI: 10.13189/ujer.2017.050619
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Participating in Recreational Activities on Quality of Life and Job Satisfaction

Abstract: The aims of this study were to compare the differences and determine the relationships between the scores obtained from Minnesota job-satisfaction and quality-of-life scales applied to males' ages 18 to 40 who participate in recreational activities and those who do not. The samples of the study consisted of 282 volunteers (148 of whom participate in sports and 134 of whom do not) employed in public institutions and organisations in the City of Vezirköprü in Turkey's Samsun province. The data obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The reasons for participation in recreational activities for most high school teachers are for their physical fitness, personal satisfaction, social development, recreation, fun, and enjoyment. This is also supported by the study of Aksoy et al (2017) that found those who participated in recreational activities did so because it gave quality of life and job satisfaction. Recreational activities on a weekly basis and timed recreational participation, whose schedule for recreation was twice a week.…”
Section: Resultsmentioning
confidence: 62%
“…The reasons for participation in recreational activities for most high school teachers are for their physical fitness, personal satisfaction, social development, recreation, fun, and enjoyment. This is also supported by the study of Aksoy et al (2017) that found those who participated in recreational activities did so because it gave quality of life and job satisfaction. Recreational activities on a weekly basis and timed recreational participation, whose schedule for recreation was twice a week.…”
Section: Resultsmentioning
confidence: 62%
“…According to the study of Pressman et al (2009), they found evidence of an association between having multiple types of leisure activities and psychological and physical well-being. This claim was further supported by Aksoy et al (2017), stating that the phenomenon of leisure time is said to be helpful by giving temporary independence from life's estrangements. To make time for leisure activities, the conversation partners also expressed the importance of setting work boundaries and limits.…”
Section: Fulfilling Self-preserving Needsmentioning
confidence: 90%
“…They could include leisure time activities, which encompasses sport and exercise activities, cultural activities, outdoor activities, social activities and similar activities with the purpose of improving mood as well as general health and wellness. According to Aksoy, Cankaya and Taşmektepligil (2017), recreational activities constitute the most significant area of sports activities in terms of enhancing health. However, many people and lecturers tend to delegate an insignificant place and time to recreational activities in their life due to the numerous responsibilities they undertake in a bid to earn a living, forgetting that the impulse to recreation is so fundamental and universal that it cannot be suppressed (Gulam, 2016).…”
Section: Introductionmentioning
confidence: 99%